Fears of Illness Progression and the Production of Risk: Two Ethnographic Case Studies in Northeast Thailand - Pylypa, Jen (Anthropologica, 2022)
This article considers common themes emerging from two ethnographic research projects in Northeast Thailand: one on women's reproductive health concerns, and another on chil- dren's fevers. Both projects revealed that illness experiences were substantially shaped by particular perceptions of risk - especially fears that a mild illness would progress to a fatal one - exacerbated by feelings of social vulnerability in clinical encounters. The analysis examines how experiences of risk were constructed in the context öf multiple, intersecting forces, rang- ing from "ethnomedical" perceptions to the impact of health education and prevention programs, pharmaceutical market- ing, and social inequalities between patients and health providers.